Food Quality Issues : Understanding HACCP and Other Quality Management Techniques - Giovannucci, Daniele; Satin, Morton (World Bank, Washington, DC, 2014)
This teaching tool provides a basic understanding of food quality issues in developing countries and introduces the reader to Hazard Analysis Critical Control Points (HACCP) and other dominant methodologies for improving food quality. Quality has long been a factor in the success of food trade transactions; however, recent food safety issues have propelled quality control to the forefront of international trade concerns. Now with the increasing globalization of trade, food quality is also becoming a factor in domestic markets as quality and variety compete for a buyer's attention and regulatory bodies seek to better control potential threats. This document includes the following annexes: Table of good agricultural practices; Good manufacturing practices; and Contraventions cited for U.S. Food and Drug Administration import detentions.